Genetic Factors Involved in Mandibular Prognathism. Issue 5 (July 2017) - Doraczynska-Kowalik, Anna; Nelke, Kamil H.; Pawlak, Wojciech; Sasiadek, Maria M.; Gerber, Hanna
Abstract : Abstract: Mandibular prognathism is defined as an abnormal forward projection of the mandible beyond the standard relation to the cranial base and it is usually categorized as both a skeletal Class III pattern and Angle Class III malocclusion. The etiology of mandibular prognathism is still uncertain, with various genetic, epigenetic, and environmental factors possibly involved. However, many reports on its coexistence in both twins and segregation in families suggest the importance of genetic influences. A multifactorial and polygenic background with a threshold for expression or an autosomal dominant mode with incomplete penetrance and variable expressivity are the most probable inheritance patterns. Linkage analyses have, thus far, shown the statistical significance of such loci as 1p22.1, 1p22.3, 1p32.2, 1p36, 3q26.2, 4p16.1, 6q25, 11q22, 12pter-p12.3, 12q13.13, 12q23, 12q24.11, 14q24.3 to 31.2, and 19p13.2. The following appear among candidate genes: MATN1, EPB41, growth hormone receptor, COL2A1, COL1A1, MYO1H, DUSP6, ARHGAP21, ADAMTS1, FGF23, FGFR2, TBX5, ALPL, HSPG2, EVC, EVC2, the HoxC gene cluster, insulin-like growth factor 1, PLXNA2, SSX2IP, TGFB3, LTBP2, MMP13/CLG3, KRT7, and FBN3. On the other hand, MYH1, MYH2, MYH3, MYH7, MYH8, FOXO3, NFATC1, PTGS2, KAT6B, HDAC4, and RUNX2 expression is suspected to be involved in the epigenetic regulations behind the mandibular prognathism phenotype.